Epithelial-Mesenchymal Transition and Metabolic Switching in Cancer: Lessons From Somatic Cell Reprogramming - Lai, Xiaowei; Li, Qian; Wu, Fang; Lin, Jiechun; Chen, Jiekai; Zheng, Hui; Guo, Lin (Frontiers in Cell and Developmental Biology, 2020)
Epithelial-mesenchymal transition (EMT) and its critical roles during cancer progression have long been recognized and extensively reviewed. Recent studies on the generation of induced pluripotent stem cells (iPSCs) have established the connections among EMT, energy metabolism, DNA methylation, and histone modification. Since energy metabolism, DNA methylation, and histone modification are important for cancer development and there are common characteristics between cancer cells and stem cells, it is reasonable to identify mechanisms that have been established during both reprogramming and cancer progression. In the current review, we start from a brief review on EMT and related processes during cancer progression, and then switch to the EMT during somatic cell reprogramming. We summarize the connection between EMT and metabolic switch during reprogramming, and further review the involvements of DNA methylation and cell proliferation. The connections between EMT and mesenchymal-epithelial transition (MET) and cellular aspects including DNA methylation, histone modification and energy metabolism may provide potential new targets for cancer diagnosis and treatment.